Association between High Density Lipoprotein (HDL) and Glycosylated Haemoglobin (HbA1c) in Type 2 Diabetes Mellitus Patients Undergoing Angiography for Acute Coronary Syndrome (Academia Journal of Medicine, 2021)
Background: To evaluate association between high density lipoprotein (HDL) and glycosylated hemoglobin (HbA1c) in type 2 diabetes mellitus patients undergoing angiography for Acute Coronary Syndrome (ACS). Subjects and Methods : Type 2 Diabetic patients who presented with Acute Coronary Syndrome were subjected to Angiography and Comparison of HDL & HbA1c level in view of single vessel or multi vessel Coronary Artery Disease was done to Evaluate association/correlation between HDL & HbA1c level with single/multi vessel Coronary Artery Disease. Result: In present study out of 90 subjects who have undergone C.A.G, 29 (32.22%) had S.V.D and 61 (67.78%) had M.V.D. In present study no. of male patients with S.V.D was 22 (75.86%) and females were 7 (24.14%). Whereas, no. of male patients with M.V.D were 45 (73.77%) and females were 16 (26.23%). Maximum no. of patients with S.V.D belong to age group 8.5. Among those with Multi vessel disease, 68.85% (n=42) had HbA1c >8.5 and 31.15% (n=19) had HbA1c of 6.5 to 8.4. There was significant inverse correlation present between level of H.D.L and number of vessel involved. Most of the patients with L.D.L ≥100 had Multi vessel disease (n=53, 86.99%). Conclusion: The severity of A.C.S, as measured by a single or multi-vessel disease on coronary angiography, is directly linked to poor glycemic management, as measured by a higher HbA1c. The severity of A.C.S is also linked to an abnormal lipid profile, such as elevated L.D.L and low-H.D.L.
Keywords: High Density Lipoprotein; Glycosylated Haemoglobin,; Diabetes Mellitus